Analiza porównawcza działalności przedsiębiorstw "A" i "B" - Karmowska, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
This work aims at the comparative economic analysis of two forest inspectorates. They manage among others the forest economy, the construction and maintenance of the forest tracts and the amelioration facilities as well as the supervision of the forest administration in the woods not owned by the State. The investigation period includes the years 2002-2005. The source data of the analyzed firms were used. The analysis was based on the selected indexes. The analyzed forest inspectorates 'A' and 'B' administer similar areas of about 19.000 ha each. The average yearly employment in the analyzed period equalled 5.476 people. The administration of the forest inspectorate involves the implementation of the sustainable development principle. The comparative analysis of the balance for the years 2002-2005 in both investigated objects indicates the same relations between the assets and liabilities. The structure of assets in both cases indicates a considerable prevalence of the fixed over the movables. The rate of return indicates profits in the forest inspectorates administration in the entire period. The administration effectiveness also indicates beneficial trends in those changes. The average collection and liabilities periods improved, and so did the inventory turnover in each analyzed period. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 249-257